If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9x+4=2x-59
We move all terms to the left:
9x+4-(2x-59)=0
We get rid of parentheses
9x-2x+59+4=0
We add all the numbers together, and all the variables
7x+63=0
We move all terms containing x to the left, all other terms to the right
7x=-63
x=-63/7
x=-9
| 6w-2(2w-1)=14 | | 2(4x-4.9)=2x-9.8 | | 4^10/4^m=4^5 | | (b-8)÷8=(b-9)÷2 | | 500x-0.09=700x+0.05 | | y-5.6=6 | | 3x=40+(x+30) | | 8x+7.44=4x+14 | | 7x+17+13=65 | | y/3=y/9+8/3 | | 9/4-y/9=7/36 | | E^(x^2-1)=42 | | 13/12z=1/6 | | z-3=z+5 | | E^x^2-1=42 | | 3n-5=2n+12 | | 8n+6n^2=0 | | -3n-4-2n=27 | | -3+10=14x-5-13x | | b-8÷8=b-9÷2 | | 9x^2+15x-70=0 | | 9x+15x-70=0 | | 2x-5500=x | | 13x-8=25-2x | | 2x-19=x-40 | | 8(9-f)=0 | | 2x-x=5500 | | 2s-4s+5=10 | | 22.4-x=25 | | 43/7x+5=55 | | 5t+71=96 | | 9x-10+x-5x+1=14+5x-8-1 |